CRYPTOCURRENCY - Juli Meliza; Isfenti Sadalia (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
Cryptocurrency, or crypto is an alternative medium of exchange. Cryptocurrencies are used with security, transparency and cost-effectiveness in mind. The purpose of this paper is to analyze cryptocurrencies. In this study, the methodology used is a qualitative descriptive approach. The object of this research is cryptocurrency. The data is secondary data obtained from journal articles on the database of reputable journal websites. Regarding the characteristics of money, cryptocurrencies are acceptable, but from an economic perspective, cryptocurrencies do not fully meet the characteristics of currencies due to high price volatility. Research findings are based on journal articles. Further discussion regarding the viewpoint of Islamic economics will be a good input to enrich the research. This study also includes implications related to the opportunities and risks of cryptocurrencies that can be discussed for the development of cryptocurrencies with cryptographic techniques in the future. The implication of this paper is that cryptocurrency is the nature of money and not as a speculative instrument. This paper discusses cryptocurrencies specifically from an economic point of view